The Spiritual Journals of Warren Felt Evans : From Methodism to Mind Cure - Evans, W. F. (Warren Felt) (Religion in North America., 2016)
Warren Felt Evans (1817-1889) converted to Methodism while at Dartmouth College, became a minister, and spent his Methodist years as a spiritual seeker. His two extant journals, edited and annotated by Catherine L. Albanese, appear in print for the first time and reveal the inner journey of a leading American spiritual pilgrim at a critical period in his religious search. A voracious reader, he recorded accounts of intense religious experience in his journals. He moved from the Oberlin perfectionism he embraced early on, through the French quietism of Madame J. Guyon and Archbishop Fenelon, then into Swedenborgianism, spiritualism, and mind cure with distinct theosophical overtones. His carefully documented journey is suggestive of the similar journeys of the religious seekers who made their way into the burgeoning metaphysical movement at the end of the 19th century--and may shed light too on today's spirituality.